2014
DOI: 10.1002/jmv.24074
|View full text |Cite
|
Sign up to set email alerts
|

Detection of occult hepatitis C virus among healthy spouses of patients with HCV infection

Abstract: The criterion standard for the diagnosis of occult hepatitis C virus (HCV) infection is detection of HCV-RNA in liver cells. However, because of the invasive nature of liver biopsy, other methods have been studied. The present study aimed to identify subjects with occult HCV-4 infection among healthy sexual partners of patients with chronic HCV-4 infection by detecting HCV-RNA in peripheral blood mononuclear cells (PBMCs) using real-time polymerase chain reaction (PCR). Fifty healthy Egyptian spouses of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
2
5
1
Order By: Relevance
“…Interestingly, a recent study was conducted at Ain Shams University, Egypt, to identify OCI with genotype‐4 among healthy Egyptian sexual partners of patients with chronic HCV‐4 infection using real‐time PCR detection of HCV‐RNA in PBMCs. The prevalence of occult HCV‐4 infection in these partners was 4% [Shazly et al, ]. This rate is similar to ours but with a different selection criteria.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, a recent study was conducted at Ain Shams University, Egypt, to identify OCI with genotype‐4 among healthy Egyptian sexual partners of patients with chronic HCV‐4 infection using real‐time PCR detection of HCV‐RNA in PBMCs. The prevalence of occult HCV‐4 infection in these partners was 4% [Shazly et al, ]. This rate is similar to ours but with a different selection criteria.…”
Section: Discussionsupporting
confidence: 85%
“…Detection hepatitis C virus RNA in plasma in this study (1.4%), this reveal false negative among negative result for hepatitis C virus Antibodies which done already in blood bank laboratory, because of error technique or blood donors in serocoversion period before appearance antibodies, so the true detection of OCI in our study was nine out of 140 (6.4%). This result closed to other investigation of Shazly et al (2015) [21] who documented that OCI was 4% in healthy Egyptian individual partners of patients infected with chronic HEPATITIS C VIRUS genotype 4 infection. Also in hemodialysis patients Abdurrahman et al (2016) [22] detect OCI (3.7%) in 81 at Mania-Egypt, Also Maria de la Luz Martinez-Rodríguez 2018 [23] in Mexico City documented OCI 3.4% in blood donors Samples, Lin H 2016 documented OCI 2.2%in China [24] and Quinoa JA 2016 OCI is 2.1% Spain [25].…”
Section: Discussioncontrasting
confidence: 48%
“…We determined a strong association between homosexual relationships and OCI (OR = 5.52), which suggests that a homosexual relationship is a risk factor. Shazly et al reported that 4% of healthy spouses of CHC patients have OCI, supporting the notion that sexual transmission of OCI occurs [ 27 ]. In the present study, 97.4% were heterosexual and 3.2% of these were positive for OCI, which is in agreement with what was previously reported.…”
Section: Discussionmentioning
confidence: 81%